2012
DOI: 10.1038/oby.2012.107
|View full text |Cite
|
Sign up to set email alerts
|

Using Facebook and Text Messaging to Deliver a Weight Loss Program to College Students

Abstract: Objective: Between 31 and 35% of the college-aged population is overweight or obese, yet few weight loss trials for this population have been conducted. This study examined the feasibility, acceptability, and initial efficacy of a technology-based 8-week weight loss intervention among college students. Design and Methods: Students (N ¼ 52) were randomly assigned to one of the three arms: Facebook (n ¼ 17); Facebook Plus text messaging and personalized feedback (n ¼ 18); Waiting List control (n ¼ 17), with asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
167
0
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(175 citation statements)
references
References 28 publications
3
167
0
5
Order By: Relevance
“…Most studies were conducted in the United States of America (N ¼ 18) (Agras et al, 1990;Allen et al, 2013;Appel et al, 2011;Burke et al, 2012;Cadmus-Bertram et al, 2013;Chambliss et al, 2011;Goulis et al, 2004;Harvey-Berino et al, 2010;Haugen et al, 2007;Herring Jeffery et al, 2003;Johnston et al, 2012;Napolitano et al, 2013;Norman et al, 2013;Sherwood et al, 2006Sherwood et al, , 2010Shuger et al, 2011;Svetkey et al, 2008). Four studies were conducted in Australia (Blomfield et al, 2014;Collins et al, 2012;Hutchesson et al, 2014;Morgan et al, 2011), one study in China (Lin et al, 2014), one study in Japan (Tanaka et al, 2010), one study in the United Kingdom (Donaldson et al, 2014) and two studies in Germany (Luley et al, 2011;Mehring et al, 2013).…”
Section: Study Characteristicsmentioning
confidence: 97%
See 3 more Smart Citations
“…Most studies were conducted in the United States of America (N ¼ 18) (Agras et al, 1990;Allen et al, 2013;Appel et al, 2011;Burke et al, 2012;Cadmus-Bertram et al, 2013;Chambliss et al, 2011;Goulis et al, 2004;Harvey-Berino et al, 2010;Haugen et al, 2007;Herring Jeffery et al, 2003;Johnston et al, 2012;Napolitano et al, 2013;Norman et al, 2013;Sherwood et al, 2006Sherwood et al, , 2010Shuger et al, 2011;Svetkey et al, 2008). Four studies were conducted in Australia (Blomfield et al, 2014;Collins et al, 2012;Hutchesson et al, 2014;Morgan et al, 2011), one study in China (Lin et al, 2014), one study in Japan (Tanaka et al, 2010), one study in the United Kingdom (Donaldson et al, 2014) and two studies in Germany (Luley et al, 2011;Mehring et al, 2013).…”
Section: Study Characteristicsmentioning
confidence: 97%
“…The total sample size was N ¼ 5747. The majority of the studies were randomised controlled trials (RCT's) (Agras et al, 1990;Allen et al, 2013;Appel et al, 2011;Blomfield et al, 2014;Burke et al, 2012;Cadmus-Bertram et al, 2013;Chambliss et al, 2011;Collins et al, 2012;Donaldson et al, 2014;Goulis et al, 2004;Harvey-Berino et al, 2010;Herring et al, 2014;Hutchesson et al, 2014;Jeffery et al, 2003;Johnston et al, 2012;Lin et al, 2014;Luley et al, 2011;Morgan et al, 2011;Napolitano et al, 2013;Norman et al, 2013;Sherwood et al, 2006Sherwood et al, , 2010Shuger et al, 2011;Svetkey et al, 2008;Tanaka et al, 2010). One study was a cluster-randomised trial (Mehring et al, 2013), one study a quasiexperiment (Haugen et al, 2007) and one a controlled cohort study (Donaldson et al, 2014).…”
Section: Study Characteristicsmentioning
confidence: 98%
See 2 more Smart Citations
“…More recently, Schein et al 35 conducted a systematic literature review and identified only 1 controlled intervention study on social media and health outcomes and it failed to isolate the impact of social media in a larger communication campaign. Since that review, Napolitano et al 39 conducted a small randomized clinical trial of weight loss program delivered through a private Facebook group, a similar Facebook group plus text messaging and personalized feedback, and a wait list control condition among college students. At 4-and 8-week follow-up, participants in the Facebook Plus group had significantly more weight loss than members of either the Facebook or wait list comparison groups.…”
Section: Evidence For the Effectiveness Of Sns For Improving Healthmentioning
confidence: 99%